2018
DOI: 10.3126/nepjoph.v9i2.19259
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of primary peripheral posterior capsular opacification after cataract surgery and posterior capsular opacification in the patients implanted with foldable intraocular lenses

Abstract: PPPCO is a frequent occurrence in mature cataract and there is a higher incidence of PCO in PPPCO patients implanted with hydrophilic IOL than with hydrophobic IOL. Therefore, hydrophobic IOL should be considered for patients discovered to have PPPCO during cataract removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…A total of 1400 eyes undergoing cataract surgery with peripheral pre-existing PCO (PPPCO) were either implanted with a hydrophobic or hydrophilic IOL. PPPCO is often seen in the developing world due to the late presentation of patients and in some cases of blunt ocular trauma [61,62]. The study found PPPCO patients implanted with a hydrophilic IOL had a higher propensity towards PCO development than those implanted with a hydrophobic IOL.…”
Section: Intraocular Lens-associated Risk Factorsmentioning
confidence: 82%
See 1 more Smart Citation
“…A total of 1400 eyes undergoing cataract surgery with peripheral pre-existing PCO (PPPCO) were either implanted with a hydrophobic or hydrophilic IOL. PPPCO is often seen in the developing world due to the late presentation of patients and in some cases of blunt ocular trauma [61,62]. The study found PPPCO patients implanted with a hydrophilic IOL had a higher propensity towards PCO development than those implanted with a hydrophobic IOL.…”
Section: Intraocular Lens-associated Risk Factorsmentioning
confidence: 82%
“…The choice of material, design, and function of the IOL can greatly impact risk of developing PCO. A prospective study conducted by Joshi [61] exemplifies the importance of IOL selection for patients with pre-existing conditions. A total of 1400 eyes undergoing cataract surgery with peripheral pre-existing PCO (PPPCO) were either implanted with a hydrophobic or hydrophilic IOL.…”
Section: Intraocular Lens-associated Risk Factorsmentioning
confidence: 99%
“…PCO is a common long-term complication of cataract phacoemulsification. Multiple studies have investigated various strategies to prevent and treat PCO, including surgical techniques, drug research [ 12 ] and intraocular lens design [ 13 , 14 ]. Objective quantitative measurement of PCO is crucial in evaluating the effectiveness of such interventions and assessing the clinical course.…”
Section: Discussionmentioning
confidence: 99%
“…1 Masood 2 reported an incidence of 31% in hypermature cataracts. In a recent study, Joshi 3 reported an incidence of 5.7% of pre-existing or primary posterior capsular opacity in patients undergoing phacoemulsification of senile cataract. It was established that it was caused by a mature cataract in 47.5%, a posterior subcapsular cataract in 36.2% and a posterior polar cataract in 16.2% of the cases.…”
Section: Introductionmentioning
confidence: 99%